Employee development strategies as a means of improving performance in healthcare organizations: A literature review - Siti Rahima Kiram; Salsabila Firdausi; Evita Mutiara; Acim Heri Iswanto (PT WIM Solusi Prima, 2026)
Healthcare organizations require a qualified workforce to provide efficient, safe, and high-quality services; therefore, employee development is a crucial step in improving organizational performance. This study aims to synthesize various research findings to understand effective employee development methods and their impact on the performance of healthcare organizations by conducting a literature review through a search of articles from various data sources between 2021 and 2025. The results of the analysis indicate that human resource development strategies—including systematic workforce planning, continuous training, career development, talent management implementation, and a clear performance evaluation system accompanied by feedback—have been proven to enhance the capabilities, motivation, and productivity of healthcare workers.However, in practice, challenges remain, such as a mismatch between workforce qualifications, suboptimal post-training evaluations, a lack of communication across management levels, and a career development system that remains disorganized. Additionally, supporting factors such as supportive leadership, a positive work environment, effective communication, and recognition play a crucial role in enhancing the positive impact of employee development on performance. This study concludes that employee coaching that is coordinated, sustainable, and tailored to the organization’s needs and advancements in health technology is the key to achieving superior performance in healthcare organizations and providing quality services to the public.